Strategies for biosafety and minimizing the risk of health problems in laboratories of a university center - Kirchner, Rosane Maria; Loebens, Luíza; Scherer, Mônica Elisa; Ochôa, Priscila Ozelame; Chaves, Magda Antunes de; Silinske, Jaqueline; Soares, Adriana Ribas (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010745 This project provided to study environmental risks triggering of aggravating health problems in Teaching and Research laboratories in a university center and to aware workers from these places in order to develop procedures to minimize the risk of personal accidents and environmental contamination. There were lectures, interviews, distribution of educational material and preparation of risk maps, which are displayed in each of the laboratories involved. From the interviews it was found that 86.6% of the interviewees claimed they had no knowledge of biosecurity issues and risks to health and they haven’t attended any course or training on this subject. Regarding the PPE, most of them always wear long robes and gloves, and often smocks. 73.3% always make use of leather or rubber boots. The preparation of the risk map, lectures, brochure and information on PPE served as an educational process enabling socialization concepts and biosafety as well as awareness of workers on this issue.